Upaya Meningkatkan Hasil Belajar IPS dengan Menerapkan Model Role Playing Berbantuan Media Papan Flanel pada Peserta Didik Kelas IV-C SDN-1 Sabaru Palangkaraya Tahun Pelajaran 2016/2017 - Orhan Orhan; Siti Aminah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to describe the learning activities of students in social studies learning by applying role-playing models assisted by flannel board media in class IV-C SDN-1 Sabaru Palangkaraya 2016/2017 Academic Year, as well as improving student learning outcomes in social studies learning by applying role models playing aided by flannel board media in class IV-C SDN-1 Sabaru Palangkaraya Academic Year 2016/2017. The type of research used by researchers is Classroom Action Research (CAR), with the research subjects all IV-C class students of SDN-1 Sabaru Palangkaraya totalling 26 students. Data collection techniques in this study used tests and observations. Data analysis using qualitative and quantitative data analysis. The results of this study indicate that the activity of social studies learning students of class IV-C of SDN-1 Sabaru Palangkaraya increased by an average of 3.43 which included good criteria, learning outcomes of students of class IV-C of SDN-1 Sabaru Palangkaraya increased from the pretest results the average value of 62.11 with classical completeness was 46.15%, while the post-test results in the first cycle averaged 76.53 with 100% classical completeness.